Analýza stavu informačního systému ve firmě a návrh možného zlepšení - Fikr, Radovan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Bakalářská práce analyzuje část IT infrastruktury ve firmě a navrhuje pro tuto konkrétní vybranou oblast nové systémové řešení, kterým je možné zajistit technické a ekonomické zlepšení. Tato práce popisuje návrh na optimalizaci a konsolidaci serverů s využitím virtuálního prostředí. Součástí je i popis jednotlivých technologií virtuálního prostředí a jejich výhody. Podrobně se zaměřuje na oblast konsolidace serverů, která je rozhodující pro IT infrastrukturu v organizaci. Na závěr je navrženo jedno konkrétní řešení s vyhodnocením přínosů pro podnik.

The Bachelor's Work analyses a part of IT infrastructure in the company and suggests new system solutions for the particular selected area by which it is possible to guarantee both technical and economical improvement. This work describes the proposal for the optimalization and consolidation of the servers with the utilization of the virtual environment. The part is also the description of individual technologies of virtual environment and their advantages. It focuses detailed on the area of consolidation of the servers which is decisive for IT infrastructire in the organization. At the end is suggested one particular solution with the evaluation of the advantages for the company.
The Analysis Condition Information System in the Company and the Proposal of Possible Improvement
Keywords: Hyper-V; konsolidace; Microsoft; virtualizace; VMware; Windows Server; Hyper-V; consolidation; Microsoft; virtualisation; VMware; Windows Server